2012
DOI: 10.5194/acp-12-2077-2012
|View full text |Cite
|
Sign up to set email alerts
|

The influence of boreal biomass burning emissions on the distribution of tropospheric ozone over North America and the North Atlantic during 2010

Abstract: Abstract.We have analysed the sensitivity of the tropospheric ozone distribution over North America and the North Atlantic to boreal biomass burning emissions during the summer of 2010 using the GEOS-Chem 3-D global tropospheric chemical transport model and observations from in situ and satellite instruments. We show that the model ozone distribution is consistent with observations from the Pico Mountain Observatory in the Azores, ozonesondes across Canada, and the Tropospheric Emission Spectrometer (TES) and … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
86
1

Year Published

2013
2013
2018
2018

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 96 publications
(91 citation statements)
references
References 66 publications
4
86
1
Order By: Relevance
“…Boreal forest fires are also an important source of PAN and, due to their proximity to the Arctic, plumes can be transported to high latitudes during the spring and summer months (Brock et al, 2011;Singh et al, 2010). Whilst little O 3 production appears to occur close to boreal fires (Alvarado et al, 2010;Paris et al, 2010), several recent studies have shown O 3 production downwind from boreal fires in the Arctic during the summer months (Wespes et al, 2012;Parrington et al, 2012;Thomas et al, 2013). Nevertheless, O 3 production is higher in air masses influenced by anthropogenic emissions.…”
Section: Arcticmentioning
confidence: 96%
See 1 more Smart Citation
“…Boreal forest fires are also an important source of PAN and, due to their proximity to the Arctic, plumes can be transported to high latitudes during the spring and summer months (Brock et al, 2011;Singh et al, 2010). Whilst little O 3 production appears to occur close to boreal fires (Alvarado et al, 2010;Paris et al, 2010), several recent studies have shown O 3 production downwind from boreal fires in the Arctic during the summer months (Wespes et al, 2012;Parrington et al, 2012;Thomas et al, 2013). Nevertheless, O 3 production is higher in air masses influenced by anthropogenic emissions.…”
Section: Arcticmentioning
confidence: 96%
“…It is worth noting that there are direct tropospheric ozone retrievals from satellite data (Liu et al, 2006). The AMMA campaign (Redelsperger et al, 2006) and associated analysis performed with the in situ MOZAIC and SHADOZ data (Thompson et al, 2003a, b) have revealed a somewhat different feature of ozone distribution (both in terms of amount of the tropospheric columns G. Liu et al: A global tropospheric ozone climatology from trajectory-mapped ozone sounding tabase (1160 sites total), with correlation coefficients genally between 0.6 and 0.7 (Tarasick et al, 2010). Figure 1 indicates that although the 4-day trajectory mapng greatly expands the spatial coverage of the ozonesonde easurements, there are still places where no ozone mearement is available.…”
Section: A Climatological View Of Ozone/linkages Across the Scalesmentioning
confidence: 99%
“…BORTAS took place across several regions of Canada between the 12 July and 3 August in both 2010 and 2011, although activity during the 2010 deployment (BORTAS-A) was limited to ground-based measurements at a main ground station located at Dalhousie University in Halifax, Nova Scotia, along with ozonesonde launches from a network of seven sites across central and eastern Canada and supporting satellite observations (Parrington et al, 2012). Airborne measurements were carried out during BORTAS-B in 2011, providing all data contributing towards this study.…”
Section: Introductionmentioning
confidence: 99%
“…However, other recent studies suggest that positive dO 3 /dCO is not always an indicator of an ozone-producing region [33,34], especially in cases where there is substantial CO loss in a plume due to intense production of OH from ozone. Parrington et al [35,36] discussed in detail ozone production in fire plumes in North America and the northern Atlantic. Their analysis suggests that plumes younger than 4 days feature low ozone production efficiencies that increase for older plumes, associating this feature with the relatively quick reduction of aerosol loading with plume age.…”
Section: Gasesmentioning
confidence: 99%